Chemistry and pharmacology of naturally occurring bioactive compounds - Brahmachari, Goutam (CRC Press, 2013)
"Natural products play crucial roles in modern drug development and constitute a prolific source of novel lead compounds or pharmacophores for ongoing drug discovery programs. Chemistry and Pharmacology of Naturally Occurring Bioactive Compounds presents cutting-edge research in the chemistry of bioactive natural products and demonstrates how natural product research continues to make significant contributions in the discovery and development of new medicinal entities."--Page 4 of cover.